Technical Readiness of Prescriptive Analytics Platforms: A Survey - Niederhaus, Marvin; Migenda, Nico; Weller, Julian; Schenck, Wolfram; Kohlhase, Martin (2024 35th Conference of Open Innovations Association (FRUCT))

Challenges and Research Needs in the Offer Phase of Special Purpose Machinery and Plant Engineering – A Qualitative Study with Industry Experts - Wilke, Daria; Mansheim, Johanna; Dumitrescu, Roman (IEEE Engineering Management Review)

PID-Gen: Towards an Algorithm for the Generation of Random P&IDs - Merkelbach, Silke; Heuwinkel, Tim; Dumitrescu, Roman (2024 IEEE 29th International Conference on Emerging Technologies and Factory Automation (ETFA))

Investigation of validation methods for system design in the B2B sector - Humpert, Lynn; Wilke, Daria; Tissen, Denis; Rummney, Johannes; Anacker, Harald; Dumitrescu, Roman (2024 IEEE International Systems Conference (SysCon))

Framework for the Selection of Systems Engineering Modelling Languages and Methods for Special Purpose Machinery - Wilke, Daria; Humpert, Lynn; Suwal, Pragita; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Intelligent Part Comparison in Computer Aided Design - Hanke, Fabian; Moallim, Karan; Bernijazov, Ruslan; Demir, Riza; Brunnhausser, Jorg; Dumitrescu, Roman; Lindow, Kai (Proceedings of NordDesign 2024)

Numerical modeling of clamp load relaxation of plastic nuts under varying moisture and fiber content - Wippermann, Jan; Meschut, Gerson
This study presents a numerical approach using a 3D finite element model to quantify the remaining clamp load of a plastic nut joint after a specific time. The viscoelastic relaxation of a thermoplastic nut, which is predominantly screwed on a welding stud, is described by a material card using Prony Series. Prony Series are derived from experimental Dynamical Mechanical Analysis with different moisture and fiber contents of the thermoplastic. Since plastic nuts usually do not have preformed threads, the increased temperatures and resulting stresses from the thread-forming process are considered in the simulation. Firstly, the FE model is verified by substrate stress relaxation tests. Subsequently, experimental clamp load measurements with miniature compression load cells verify the clamp load prediction. Finally, the developed model is used to analyze the clamp load distribution within the threads

Effect of Water Absorption on the Clamp Load of Plastic Nuts - Wippermann, Jan; Meschut, Gerson (Proceedings of the Munich Symposium on Lightweight Design 2023)

Anwendung und Integration des Application Lifecycle Managements im Produktlebenszyklus-Ergebnisse einer Industrie-Studie - Wyrwich, Fabian; Tschirner, Christian; Bohnenkamp, Tinus; Hovemann, Aschot; Dumitrescu, Roman (Tag des Systems Engineering 2024)

Portals across domains: A data analysis task and documentation canvas for data-driven model-based systems engineering - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman

Messbare Erfolgskriterien von Systems Engineering - Wilke, Daria; Grote, Eva-Maria; Schierbaum, Anja; Dumitrescu, Roman (Tag des Systems Engineering 2024)

Analyse des Ein- und Überdrehmoments von Kunststoffmuttern in Abhängigkeit von der Luftfeuchtigkeit - Wippermann, Jan; Meschut, Gerson (JOINING PLASTICS)

Interaktive Inbetriebnahme von Steuerungen und Regelungen für partiell bekannte dynamische Systeme mittels Gauß-Prozess-Regression - Hesse, Michael
Die Inbetriebnahme von Steuerungen und Regelungen stellt sicher, dass ein mechatronisches System ordnungsgemäß funktioniert und den Anforderungen gerecht wird. Der modellbasierte Entwurf basiert auf einem genauen Simulationsmodell. Allerdings ist dieser klassische Weg bei komplexen Systemen oft nicht praktikabel, da die analytische Modellierung zu kompliziert und zeitaufwendig ist. Diese Forschungslücke wird durch Verfahren adressiert, die eine effiziente und sichere Inbetriebnahme ermöglichen. Diese Verfahren kombinieren Regelungstechnik und Reinforcement Learning und nutzen vorhandenes Wissen über die Regelungsaufgabe, um Korrekturen basierend auf Messdaten und der probabilistischen Gauß-Prozess-Regression vorzunehmen. Das Vorwissen kann als teilweise bekanntes physikalisches Modell oder als Steuerungsfunktion vorliegen. Anwendungsbeispiele sind der Ultraschalldrahtbondprozess, verschiedene Pendelsysteme und ein Hexapod. Eine angepasste Bayessche Optimierung wird zur Identifikation einer Steuerparametrisierung für das Ultraschallbonden eingesetzt. Außerdem wird eine hybride Optimalsteuerung für das Doppelpendel auf einem Wagen entwickelt und erfolgreich validiert. Fur einen Hexapod zur Fahrzeugachsprüfung wird eine hybride Zustandslinearisierung formuliert und ein Funktionsnachweis im Rahmen einer Simulation erbracht. Die Einhaltung technischer Rahmenbedingungen und stabiles Systemverhalten werden durch probabilistische Pradiktionen gewährleistet. In allen Anwendungsfällen wird eine Steigerung der Effizienz und Güte erzielt.

Entwicklung einer Methode zur Prognose der Verschraubungsparameter von Kunststoffmuttern - Wippermann, Jan; Meschut, Gerson (14 Gemeinsames Kolloquium Zur Mechanischen Fügetechnik)

Time autonomy in personnel planning: Requirements and solution approaches in the context of intelligent scheduling from a holistic organizational perspective Zeitautonomie in der Personaleinsatzplanung: Anforderungen und Lösungsansätze im Rahmen einer intelligenten Planung aus ganzheitlicher organisationaler Perspektive - Latos, Benedikt; Buckhorst, Armin; Kalantar, Peyman; Bentler, Dominik; Gabriel, Stefan; Dumitrescu, Roman; Minge, Michael; Steinmann, Barbara; Guhr, Nadine (Zeitschrift für Arbeitswissenschaft)
Abstract Traditional work models often need more flexibility and time autonomy for employees, especially in manufacturing. Quantitative approaches and Artificial Intelligence (AI) applications offer the potential to improve work design. However, current research does not entirely focus on human-centric criteria that enable time autonomy. This paper addresses this gap by developing a set of criteria to evaluate intelligent personnel planning approaches based on their ability to enhance time autonomy for employees. Existing quantitative approaches are not sufficient to fully integrate the developed criteria. Consequently, a novel model approach is proposed in an attempt to bridge the gap between current practices and the newly developed criteria. This two-stage planning approach fosters democratization of time autonomy on the shopfloor, moving beyond traditional top-down scheduling. The paper concludes by outlining the implementation process and discusses future developments with respect to AI for this model approach. Practical Relevance : In order to make working conditions on the shopfloor in high-wage countries more attractive, an alternative organization of shift work is needed. Intelligent planning approaches that combine traditional operations research methods with artificial intelligence approaches can democratize shift organization regarding time autonomy. Planning that takes both employee and employer preferences into account in a balanced way will strengthen the long-term competitiveness of manufacturing companies in high-wage countries and counteract the shortage of skilled labor.

Evolving Roles in Systems Engineering —‐ Insights from Germany's Mechanical and Plant Engineering Sector - Kaiser, Lydia; Wilke, Daria; Förster, Felix; Köhler, Ingmarie; Dumitrescu, Roman (INCOSE International Symposium)
Abstract Systems Engineering is developing differently in each sector and region. In German industry, especially in mechanical and plant engineering, Systems Engineering is of major importance. The introduction of Systems Engineering raises the question of which roles and competencies are required. This article examines the evolution of roles in Systems Engineering from a German perspective. Based on a literature review, the evolution of the identified Systems Engineering roles over time is shown, starting with the seminal publication by Sheard in 1996. It points out that only minimal adjustments and occasional role renaming have occurred. However, the review shows a common understanding of essential areas of responsibility within the SE and changes over time. The next step is to examine the current understanding of Systems Engineering roles in the industry. A quantitative analysis of job postings in Germany reveals a diverse interpretation of the term 'Systems Engineer; more than half of the positions cannot be categorized according to the INCOSE definitions. The job postings are used to determine which tasks are associated with the job, how often they occur, and in what combination. The primary responsibilities of systems engineers include creating and managing requirements, architecture processes, validation, and verification processes, and coordinating with customers and stakeholders. Finally, three representative companies from the mechanical and plant engineering sector were selected to analyze existing roles and tasks. From this, a common understanding of tasks and responsibilities is combined and organized into clusters. These are used by the companies to locate and thus derive their roles. The result is in an integrative approach that enables companies, especially in the midsize and medium sectors, to design the introduction in line with stakeholder demands. In summary, the industry's ongoing adaptation necessitates the evolution of Systems Engineering roles and competencies for successful and sustainable development and implementation of systems.

Influences on the Material Displacement and Compression Stresses in the Joining Process of Highly Viscous Thermal Interface Materials - Gilich, Julian; Teutenberg, Dominik; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (77th IIW Annual Assembly and International Conference on Welding and Joining)

Empowering SMEs “Harnessing the Potential of Gen AI for Resilience and Competitiveness” - Carayannis, Elias G.; Dumitrescu, Roman; Falkowski, Tommy; Zota, Nikos-Rigert (IEEE Transactions on Engineering Management)

Developing a data analytics toolbox for data-driven product planning: a review and survey methodology - Panzner, Melina; von Enzberg, Sebastian; Dumitrescu, Roman (Artificial Intelligence for Engineering Design, Analysis and Manufacturing)
Abstract The application of data analytics to product usage data has the potential to enhance engineering and decision-making in product planning. To achieve this effectively for cyber-physical systems (CPS), it is necessary to possess specialized expertise in technical products, innovation processes, and data analytics. An understanding of the process from domain knowledge to data analysis is of critical importance for the successful completion of projects, even for those without expertise in these areas. In this paper, we set out the foundation for a toolbox for data analytics, which will enable the creation of domain-specific pipelines for product planning. The toolbox includes a morphological box that covers the necessary pipeline components, based on a thorough analysis of literature and practitioner surveys. This comprehensive overview is unique. The toolbox based on it promises to support and enable domain experts and citizen data scientists, enhancing efficiency in product design, speeding up time to market, and shortening innovation cycles.

Future Robust Product Portfolio Development: Modelling Innovation Potentials in Product Portfolios - Schlegel, Michael; Just, Markus; Pfaff, Felix; Wiederkehr, Ingrid; Koldewey, Christian; Kempf, Christoph; Dumitrescu, Roman; Albers, Albert (Procedia CIRP)